Elements of the Traditional and Electronic Commercial Store - Abdul Aziz bin Saeed Aljuhni; Abdulrazzaq Jajan (International Journal of Law Research and Studies, 2024)
In this research, I wrote about the elements of traditional and electronic commercial stores in Saudi laws. Explaining the nature of the commercial store, both traditional and electronic. Then I wrote about the elements of the traditional commercial store and divided them into Tangible and moral elements. In conclusion, I talked about the material and moral elements that are excluded and disputed in the traditional commercial store, and I mentioned what is correct in the disputed elements. After that, I wrote about the privacy of the electronic commercial store - and I mentioned the word privacy in order to mention the concepts of the electronic commercial store, and not to repeat the common concepts between electronic and traditional, and not to delve into the similarities between them. I described the Tangible and moral elements of the commercial and online store and mentioned the appropriate concepts for the online store. I did not limit myself to the description, but I also analyzed texts and regulatory references. Finally, the results and recommendations were mentioned. One of the most important findings of the draft commercial transactions law is that rights and debts are considered material elements of the store. One of the most important recommendations in this research is that the Saudi legislator must rectify the conflict that I mentioned between the trade names law, “dealing in a store that does not include its trade name unless it is agreed upon in writing,” and the draft commercial transactions law. “It is permissible to dispose of the warehouse and disposal includes everything in the warehouse.
Keywords: Elements of the Traditional Store; Elements of the Electronic Store